In vitro evaluation of the radial and axial force of self-expanding esophageal stents - Hirdes, Meike M. C.; Vleggaar, Frank P.; de Beule, Matthieu; Siersema, Peter D. (Endoscopy, 2013)
Background and study aims: Technological innovation in esophageal stent design has progressed over the past decades, but the association between the mechanical properties of stent design and clinical outcome is still poorly understood. In this study the radial force and axial force of currently available stent designs were evaluated using an in vitro testing model.Methods: A total of 10 partially and fully covered self-expanding metal stents (SEMSs), a self-expanding plastic stent (SEPS), and an uncovered biodegradable stent were evaluated. Radial force and axial force were measured using a radial force measurement machine (RX500) and a force gauge in an oven at 37°C.Results: A wide range of radial force measurements were observed between the different stent designs, ranging from 4 to 83 N at 15 mm expansion. All braided nitinol stents displayed comparable mechanical characteristics with a relatively low radial force (< 150 N) that gradually decreased to 0 N during expansion, whereas plastic and metal stents that were constructed in a nonbraided manner displayed an initially high radial force (> 300 N) followed by a steep decline to 0 N during expansion. Conversely, peak axial force was relatively high for braided nitinol SEMSs (> 1.5 N), whereas nonbraided SEMSs showed a much lower peak axial force (< 1.5 N). Based on radial and axial force data, five groups of stents with comparable mechanical properties could be distinguished. Conclusions: All currently available stents have a characteristic radial and axial force pattern, which may aid in the understanding of the occurrence of specific symptoms and complications after stent placement. Nonetheless, the overall clinical behavior of a stent is probably more complex and cannot be explained by these factors alone.